Lipase-Catalyzed Synthesis of Cetyl Palmitate in the Presence of n-Hexane and Ethyl Ether - Gustavo Gealh; Maynara L. A. Santos; Marcos L. Corazza; Adrián Bonilla-Petriciolet; Fernando A. P. Voll (International Journal of Chemical Engineering)
Cetyl palmitate was produced by the esterification of palmitic acid with cetyl alcohol using n-hexane and ethyl ether as solvents and a commercial lipase as a catalyst. The effect of solvents to reagents mass ratio (0.5 : 1–3 : 1), percentage of n-hexane in the solvent mixture (0–100%), and reaction temperature (25–55°C) on the reaction rate were evaluated for a fixed amount of enzyme (1 wt% related to the total mass of substrates) in an equimolar mixture of palmitic acid and cetyl alcohol. Temperature and n-hexane percentage in the solvent had positive effects on the reaction rate. The total solvent-to-reagent mass ratio showed a negative effect on the reaction rate when a solvent mixture rich in ethyl ether was used. The higher the concentration of n-hexane, the lower the effect of the mass ratio of solvents to reagents on the reaction rate. Although the amount of ethyl ether in the solvent mixture had a negative effect on the reaction rate, it had a positive effect on the solubility of the system, that is, the more ethyl ether in the mixture, the lower the solvent to reagents mass ratio required to ensure a homogeneous mixture. A ping-pong bi-bi mechanism-based model was proposed to represent the system kinetics and was well fitted to the experimental data.